The strategic role white victimhood narratives play in maintaining white supremacy: An analysis of the Afrikaner “refugee” phenomenon in the US - Raper, Francis-Lynne (The Stellenbosch Socratic Journal, 2025)
Since early 2025 the Trump administration has granted Afrikaners refugee status and resettlement in the US. At the same time the administration cracked down on most other types of immigration towards the US and has halted refugee admissions. This article argues that white anxiety and victimhood narratives are employed by far-right political actors, Trump, and Afrikaner organisations such as AfriForum and Solidariteit to maintain an infallibility of whiteness and subsequently white supremacy. Charles Mills’s work on white supremacy is used to argue that the idea of the white victim in contemporary politics is crucial for securing whiteness as the norm and the privileged position of white people in society. Further, this article illustrates how white victimhood narratives are crucial for protecting white supremacy and that this is the primary reason Afrikaners have been awarded refugee status in the US.